Analysis of Digital Technology Adaptation Based on Cashless Society in Islamic Philantrophic Institution Weet Dhuafa Waspada - Hasibuan, M. Fawwaz Eljawahir; Nurbaiti, Nurbaiti; Inayah, Nurul (SAINTIS Publishing, 2025)
Adapting Digital Technology Based on a Cashless Society is a step taken by the Islamic philanthropic institution Dompet Dhuafa Waspada to introduce social programs by disseminating information. Cashless society in Islamic philanthropy is to simplify and speed up the donation process and so on, but this implementation also faces various challenges, such as low digital literacy among the community, resistance to change, and the need to ensure data and transaction security. The aim of this research is to examine the Adaptation of Cashless Society-Based Digital Technology used by Dompet Dhuafa. This research is qualitative research with a descriptive analysis method that focuses on primary data sources and secondary data. The results show that the adaptation of digital technology based on a cashlesssociety at DompetDhuafa Waspada hasgreat potential to increase efficiency, transparency and institutional reach. However, the success of this adaptation depends on strategic partnerships, increasing people's digital literacy, and ongoing efforts to build trust through data security and transparent reporting.